2011
DOI: 10.1177/008124631104100311
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Relationship between Students' Motivation and Academic Performance as Mediated by Effort

Abstract: This study investigated the relationship between university students' motivation and their academic performance, with effort acting as a mediating variable. The study strives to add to the body of knowledge on motivation, effort and academic performance, with specific reference to tertiary level institutions in the South African context. Motivation is separated into intrinsic motivation and extrinsic motivation, which were used as the independent variables. Academic performance is the dependent variable, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 31 publications
4
63
0
6
Order By: Relevance
“…The results are also compatible with most of the studies which are carried out in different countries and different samples, from which it can be generally infers that motivation has an important effect on academic performance in a positive way (Goodman, Jaffer, Keresztesi, Mamdani, Mokgatle, Musariri, Pires, Schlechter, 2011;Mo, 2011;Cheng, Lin and Su, 2011;Ming, Ling and Jaafar, 2011;Nishitani and Matsuda, 2011). As Ryan and Deci (2000) argue, 'to be motivated means to be moved to do something'.…”
Section: Resultssupporting
confidence: 88%
“…The results are also compatible with most of the studies which are carried out in different countries and different samples, from which it can be generally infers that motivation has an important effect on academic performance in a positive way (Goodman, Jaffer, Keresztesi, Mamdani, Mokgatle, Musariri, Pires, Schlechter, 2011;Mo, 2011;Cheng, Lin and Su, 2011;Ming, Ling and Jaafar, 2011;Nishitani and Matsuda, 2011). As Ryan and Deci (2000) argue, 'to be motivated means to be moved to do something'.…”
Section: Resultssupporting
confidence: 88%
“…[11] Lack of motivation or amotivation has also been found to be one of the important barriers to learner achievement and performance. [12] Therefore, factors that enhance motivation need to be investigated. Motivation is understood to be triggered by intrinsic or extrinsic factors.…”
mentioning
confidence: 99%
“…Correlations with academic performance tend to be higher for intrinsic motivation than extrinsic motivation, but self-determination is not as strong, or as consistent, a predictor of academic performance as either self-efficacy or learning goals (see Table 7). Goodman et al (2011) found both intrinsic and extrinsic motivation to be significantly correlated with academic performance; however, the selection of participants in this study could have introduced bias. Students were invited to take part by email, with responders being entered into a prize draw.…”
Section: Self-determination Theory (Needs-based Motivation)mentioning
confidence: 61%